INTERNALISASI NILAI-NILAI PROFIL PELAJAR PANCASILA DALAM MEMBENTUK KARAKTER PESERTA DIDIK MELALUI BUDAYA SEKOLAH ADIWIYATA - Nopi Novita; Nunu Nurfirdaus; Atang Sutisna (STKIP Subang, 2024)
Adiwiyata school culture in forming the character profile of Pancasila students. Qualitative descriptive is a research method that researchers use to obtain an overview of the formation of the character profile of Pancasila students through the Adiwiyata school culture. The research location was carried out at SD Negeri 1 Cigadung, Cigugur District, Kuningan Regency. The main sources of information in this research were the homeroom teacher and students in grades 4, 5, and 6. The canteen keeper and school custodian were additional informants. Furthermore, the key informant consisted of the school principal. Observation, interviews and documentation were used as data collection techniques. Data analysis techniques using Miles and Huberman descriptive analysis include data reduction, presentation and inference. The results of the research show that the instillation of Pancasila student profile values to shape student character through the Adiwiyata school culture was successful, as evidenced by the existence of several Adiwiyata activities that can shape the Pancasila student profile character, teach the values of caring for the environment and apply them in real life at school.